Characterization of Biodegradable Plastic Nata De Soya Using Glycerol and Palm Oil Addictive Substances - Iryani Iryani; Iswendi Iswendi; Sri Benti Etika; Citra Devira; Regi Fadila Putra (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
This research aimed to analyze the characterization of biodegradable plastic nata de soya (NDS). The addictive substance used to manufacture this plastic is a mixture of glycerol and palm oil with a saturated solution of arabic gum as an emulsifier. The volume variations are A (10:5:15) mL, B (10:10:30) mL, C (10:15:45) mL, control is (10 mL of 3% glycerol) and soaking time for NDS sheets with additives are 4, 6, and 8 days. The results showed that the highest degradation power of NDS is 87% in the variation of additive C with an immersion period of 8 days had a degree of crystallinity of 8.075%. The water resistance test was 318% in an immersion of NDS plastic with a variation of C for four days had a degree of crystallinity of 12.47%. The highest tensile strength value of plastic was 23.459 MPa in the composition of additive C with four days of immersion and had a degree of crystallinity of 13.172%.